Perceived Impact of Social Media on Students’ Health Conditions in Pokhara Valley - Subedi, Chudamani; Upadhyay, Thakur (Prithvi Journal of Research and Innovation, 2024)
The pervasive use of social media (SM) technology has brought both negative and positive impacts on health conditions among college students. This study attempts to analyse the impacts of SM on the students’ physical and mental health in Pokhara valley. Descriptive statistical tools as well as multiple regression models were applied to analyse the impacts. It showed that majority of students used Facebook, YouTube and Instagram as SM platforms for various communication and entertainment purposes. On average, the SM usage time that includes all the media types was about eight hours per day, and there was a significant difference of mean usage time between male and female students. There was a significant difference among different student groups regarding the rating on eating habit disorder due to SM. The findings suggested that the severity of impacts on the physical and mental health were significantly positively related with the SM usage time, implying that the more the students engage on SM the worse the impacts on their health conditions. However, the study also pointed out that there were positive mental health benefits in terms of SM’s role to make the social connectedness better and make them feel good about finding the right information on SM. The overall finding of the study was that the SM usage time, especially for entertainment purpose, needs to be checked for reducing the negative health impacts. However, the usefulness of SM in terms of enhanced social connectedness and finding useful information on the SM sites cannot be underestimated.